Urban Transformations Sustainable Urban Development Through Resource Efficiency, Quality of Life and Resilience - Kabisch, Sigrun; Koch, Florian; Gawel, Erik.; Haase, Annegret; Knapp, Sonja; Krellenberg, Kerstin; Nivala, Jaime; Zehnsdorf, Andreas; SpringerLink (Online service) (Cham : Springer International Publishing : Imprint: Springer, 2018)
The book addresses urban transformations towards sustainability in light of challenges of global urbanization processes and the consequences of global environmental change. The aim is to show that urban transformations only succeed if both innovative scientific solutions and practice-oriented governance approaches are developed. This assumption is addressed by providing theoretical insights and empirical evidence pointing particularly at 3 concepts or qualities which are determined here as being central for achieving urban sustainability: resource efficiency, quality of life and resilience. Urban case studies from several international research projects illustrate our conceptual approach of urban transformations towards sustainable development. Thus, the book reaches far beyond a mere additive description of single case studies. It incorporates the results of condensed synthesis, resulting from comparisons and evaluations. It provides, based on cross-cutting reflection of single casesand different scales and methods of analysis, general and transferable findings. They do not only consider the scientific sphere but deliberately go beyond it discussing transferability of knowledge into practice, governance options and the feasibility of policy strategies in order to pave the way for sustainable urban transformations to happen today and in the future.
Urban Transformations: Debates, concepts, and how our approach stands out -- Part 1: Conceptual dimensions of sustainable Urban Transformations -- Dimensions of Urban Transformations -- Linking transition theories with theories of institutions - implications for sustainable urban infrastructures between flexibility and stability -- Efficiency-equity-tradeoff as a challenge for shaping urban -- On the connection between urban sustainability transformations and multiple societal -- Part 2: Resilience and Risk Assesment -- Introduction -- Resilience and urban transformation - different sides of the same coin? -- Adapting built-up areas to climate change - assessment of effects and feasibility of adaptation measures on thermal comfort -- Climate proofing in urban planning and permitting - a key to resilient urban development -- Decision support on natural hazards management in complex urban settings -- Is risk assessment the right approach or do we need decision heuristics? -- Part 3: Quality of Life through Eco System Services -- Introduction/Synthesis -- Green infrastructure and clean air as decisive constituents of local residential quality -- Socio-spatial distribution of airborne outdoor exposures - from environmental quality to quality of life and environmental justice -- Can we enhance ecosystem services by protecting biodiversity in urban areas or do we just hope it is that easy?- Urban ecosystem services as proxy for quality of life: Santiago de Chile as a showcase city -- Urban vegetation matters -- Part 4: Governing Urban Resources -- Introduction/Synthesis -- Governing residential water demand in Amman: Sustainable transformation of urban water infrastructure in the face of unreliable public and unregulated private water supply -- Green Infrastructure -- Institutional Keys to Sustainable Urban Water Governance - Major Challenges, Fundaments and Innovative Approaches -- Challenges of the "Wärmewende" in the context of urban areas -- From shrinkage to regrowth: the nexus between urbandynamics, land use and ecosystem service provision -- The TEEB Approach for Urban Transformations: Making Ecosystem Services' Values Visible -- Part 5: Reflection and Perspectives -- Transformations concepts and implementation strategies of the Sustainable Development Goals and the New Urban Agenda -- Reflection of current state of the art of urban transformation research and further perspectives.
Keywords: Applied ecology; Sociology, Urban; Environmental management; Environmental sciences -- Social aspects; Environmental economics; Climatology; Applied Ecology; Urban Sociology; Environmental Management; Environmental Social Sciences; Environmental Economics; Climate Sciences